2014
DOI: 10.1002/cae.21607
|View full text |Cite
|
Sign up to set email alerts
|

Flip‐teaching engineering optimization, electromagnetic product design, and nondestructive evaluation in a semester's course

Abstract: Teaching practical design to students requires first a numerical course such as on finite elements and then a course on optimization. However, because of curricular constraints, it is very difficult to get students to take two courses. This paper describes a new semester's course at Michigan State University that accomplishes this through flip teaching to tackle the challenges of time. It is the flip teaching that made it possible to cover two large courses as one. The traditional order of (a) delivering theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Kim et al, 2014), reducing failure rates (Petrillo, 2016), promoting student success through doing exercises (Oddsson & Unnthorsson, 2017), engaging students without overloading them with class hours (Ravishankar et al, 2018) and so forth. Hoole et al (2015) incorporate several active learning strategies and found increased student engagement and interest. Another key dimension of student learning is self-efficacy investigated by Yan et al (2018).…”
Section: Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al, 2014), reducing failure rates (Petrillo, 2016), promoting student success through doing exercises (Oddsson & Unnthorsson, 2017), engaging students without overloading them with class hours (Ravishankar et al, 2018) and so forth. Hoole et al (2015) incorporate several active learning strategies and found increased student engagement and interest. Another key dimension of student learning is self-efficacy investigated by Yan et al (2018).…”
Section: Model Evaluationmentioning
confidence: 99%
“…Chiang and Wang (2015) found that teachers can gain access to students easily and can organize their course contents well in pursuing this approach. Teachers also utilized the method well to tackle the challenges of time constraints in covering a large volume of course material (Battaglia & Kaya, 2015;Hoole et al, 2015). Teachers too can address budget constraints in their teaching with low-cost technology aids to enhance student learning (Yelamarthi & Drake, 2015).…”
Section: Model Evaluationmentioning
confidence: 99%
“…The flip‐teaching approach is described in Ref. as a way to successfully deliver finite elements and mathematical optimization together in a semester, giving pre‐prepared programs to students learn by themselves, remaining the more detailed and complex programming assignments for the face‐to‐face teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Flipped classrooms have a major difference compared to traditional lectures in that passive lecture content (e.g., theoretical behavior, derivations) is typically assigned as independent preparation activities (e.g., watching videos, reading book chapters) completed prior to class [4]. As a result, time spent inside the classroom can be focused on active and/or application-based learning [5], and course content can be modified to increase the complexity of examples and/or introduce more rigorous concepts [6]. Flipped classrooms have shown to improve many aspects of engineering education, including increases to student interest [7], student satisfaction [8], and student attitude [9].…”
Section: Introductionmentioning
confidence: 99%